(untitled) (International journal of artificial intelligence, 2024)
The content of the "digital economy" is analyzed in the article, its main features are analyzed. Some types of digital technologies are analyzed and their influence on the development of legislation is studied. It is proposed to assess the impact of digital technologies on the mutual cooperation of business entities.